El lenguaje del éxito dentro de las fórmulas autosugestivas - Bielak-Szczotka, Kamila (Neophilologica, 2012)
The aim of this article is to present the results of the affirming statements analysis appearing in the blog of a Peruvian psychologist. We are to analyze and explain their functions, difference and predominant components from the linguistic point of view. The study focuses on the features of success language elements in auto suggestive formulas.